Spelling in Deaf, Hard of Hearing and Hearing Children With Sign Language Knowledge - Gärdenfors, Moa; Johansson, Victoria; Schönström, Krister (Frontiers in Psychology, 2019)
What do spelling errors look like in children with sign language knowledge but with variation in hearing background, and what strategies do these children rely on when they learn how to spell in written language? Earlier research suggests that the spelling of children with hearing loss is different, because of their lack of hearing, which requires them to rely on other strategies. In this study, we examine whether, and how, different variables such as hearing degree, sign language knowledge and bilingualism may affect the spelling strategies of children with Swedish sign language, Svenskt teckenspråk, (STS) knowledge, and whether these variables can be mirrored in these children’s spelling. The spelling process of nineteen children with STS knowledge (mean age: 10.9) with different hearing degrees, born into deaf families, is described and compared with a group of fourteen hearing children without STS knowledge (mean age: 10.9). Keystroke logging was used to investigate the participants’ writing process. The spelling behavior of the children was further analyzed and categorized into different spelling error categories. The results indicate that many children showed exceptionally few spelling errors compared to earlier studies, and they demonstrated good typing skills. Also, deaf children showed a tendency to rely on a visual strategy during spelling, which may result in incorrect, but visually similar, words, i.e. a type of spelling errors not found in texts by hearing children with STS knowledge. The deaf children also showed direct transfer from STS in their spelling. A sounding strategy was found in the hard-of-hearing children with STS knowledge, together with hearing children of deaf adults (CODAs), rather than a visual strategy. Nevertheless, the children with STS knowledge demonstrated fewer spelling errors in general, that may also derive from their early exposure of STS, also enabling them to use the fingerspelling strategy. Overall, this study suggests that the ability to hear and to use sign language, together and respectively, play a significant role for the spelling patterns and spelling strategies used by the children with and without hearing loss.